Impact of vaginal douching products on vaginal Lactobacillus, Escherichia coli and epithelial immune responses - Helai Hesham (Nature Portfolio, 2021)
Abstract We compared the effect of commercial vaginal douching products on Lactobacillus crispatus, L. jensenii, L. gasseri, L. iners, E. coli, and immortalized vaginal epithelial cells (VK2). All studied douching products (vinegar, iodine and baking soda based) induced epithelial cell death, and all inhibited growth of E. coli. Co-culture of vaginal epithelial cells with any of the lactobacilli immediately following exposure to douching products resulted in a trend to less human cell death. However, co-culture of epithelial cells with L. iners was associated with higher production of IL6 and IL8, and lower IL1RA regardless of presence or type of douching solution. Co-culture with L. crispatus or L. jensenii decreased IL6 production in the absence of douches, but increased IL6 production after exposure to vinegar. Douching products may be associated with epithelial disruption and inflammation, and may reduce the anti-inflammatory effects of beneficial lactobacilli.